Persepsi Guru terhadap Pelaksanaan Supervisi Pendidikan dan Perannya dalam Peningkatan Mutu Pendidikan di SMA Negeri 1 Tejakula - I.G. Ardika; I.G.A. Purnamawati; I.G.K.A. Sunu (Jurnal Administrasi Pendidikan Indonesia, 2022)
This study aims to 1) determine the implementation of supervision at SMA Negeri 1 Tejakula; 2) know the purpose of implementing Supervision at SMA Negeri 1 Tejakula; 3) know the role of the principal in the implementation of supervision at SMA Negeri 1 Tejakula; 4) knowing the efforts of the school principal in ensuring the effectiveness of the supervision program; and 5) knowing the perceptions of Tejakula 1 Public High School Teachers on the implementation of supervision at Tejakula 1 Public High School. The research was conducted at SMA Negeri 1 Tejakula. This study uses a quantitative approach, and this study uses a descriptive qualitative research design. The population in this study were all teaching and academic staff at SMA Negeri 1 Tejakula. The sample of this research is the headmaster and teachers of SMA Negeri 1 Tejakula with a total of 50 people. The research sample was determined using purposive sampling and snowball sampling techniques. Data was collected by using interviews, observation, and documentation. The data analysis technique used in this research is the qualitative data analysis technique. Qualitative research data is obtained continuously (triangulation) and is carried out always. The research results show that; 1) the implementation of the supervision program at Tejakula 1 Public High School, preceded by the monitoring process and then continued with the implementation of supervision after the supervision was carried out, an evaluation and follow-up process was carried out, 2) the Supervision program at Tejakula 1 Public High School aimed at monitoring/supervising, coaching and improving the learning process, 3) the principal of Tejakula 1 Public High School plays a vital role in supervision activities, 4) Tejakula 1 Public High School teachers' perceptions of supervision, namely having at least three views, namely supervision as an assessment tool, supervision as a coaching tool and supervision as a reflection tool.